REDEFINING GENDER THROUGH LANGUAGE: A CRITICAL STUDY OF GENDER REPRESENTATION IN ENTERTAINMENT INDUSTRY - Minnaa Ahmad; Maryam Khalid; Aatqa Aslam; Laiba Tahir (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores and compares the overall concept of gender representation in modern society by analyzing popular songs that topped the Billboard Hot 100 chart in 2019. The data was collected from the internet and critically examined through a stylistic lexical analysis. The aim of the research is to evaluate and assess how gender is currently portrayed in today’s progressive society, focusing on how celebrated artists describe both genders in their lyrics. The findings indicate that the language used to depict women has evolved compared to the past; women are no longer merely portrayed as objects of attraction but as strong, independent individuals with a significant presence in society. In some instances, women are even depicted as being more powerful and assertive than men in their interactions with the world, which represents a considerable shift in their societal portrayal. Historically, women have been objectified by popular culture, including mainstream music, television, films, and media at large.